POLA KOMUNIKASI PADA AKUN TWITTER @schcampus SEBAGAI MEDIA INFORMASI PENDIDIKAN - Winne Wardiani; Iskandar, Trias Pyrenia (Linimasa : Jurnal Ilmu Komunikasi, 2024)
ABSTRACT The presence of the @schcampus account undoubtedly becomes one of the social media platforms that significantly helps students in searching for information related to the world of campus education. In the process of exchanging educational information on the @schcampus account, it certainly has a different communication pattern. This research employs a qualitative method with a virtual ethnography research approach, which is considered feasible by the researcher to comprehensively observe the messages conveyed by @schcampus on Twitter. The communication pattern that occurs on the @schcampus base is quite interactive, ranging from diverse types of confessions ("menfess"), the use of casual language that provides flexibility for @schcampus followers, to various feedback from netizens.   Keywords: Communication Patterns, Education, Information Media, Twitter.